Justification of The Dimensions of A Small-Sized Disc Opener - Muradov Rakhimjon Hakimjonovich; Abdumannonov Bobomurod Abdusalomovich (American Journal of Botany and Bioengineering, 2026)
A study of existing seed drill designs revealed that they cannot be used for sowing grain crops in open ground in multiple rows. Based on this, a new seeder design was made. To ensure that seed drills fully and efficiently perform their intended functions, their parameters must be substantiated. This scientific article is devoted to substantiate the dimensions of the seeder parameters based on the seeder-to-soil ratio.